EVANESCENT SURFACES: THE WINDOW AS SCREEN - Soares, Maria João; Gonçalves, Clara Germana; Santos, Susana (European Scientific Journal, ESJ, 2015)
Relationship between cinema and architecture rooted in the very deviations of the passage from a century in full acceleration to a century already in post-acceleration, in which time is a decisive factor. Decisive in the material abstraction in our lives; decisive in virtuality as a pivotal factor in our lives. Our argument is centred on the possibility of us understanding two parallel courses and finding, on these courses, a single path leading to two-fold action: the opening of the cinematographic screen and the abstraction of the architectural span. As the last century progressed, both the screen and the window were starched to a limit: the first limit is abstraction – abstraction of the window and abstraction of the cinema screen, open and reclined –; the second limit is the consummation of the abstraction.